Spin–orbital coupling induced high-field decay of magneto-electroluminescence in pristine Alq3-based organic light-emitting diodes - Jia, Weiyao; Zhang, Qiaoming; Chen, Lixian; Ling, Yongzhou; Liu, Hong; Lu, Chenlei; Chen, Ping; Xiong, Zuhong (Organic electronics, 2015)
[Display omitted] •A remarkable high-field (|B|>50mT) decay of magneto-electroluminescence (MEL) was observed at room temperatures in tris(8-hydroxyquinolinato) aluminum (Alq3)-based OLEDs.•B field can increase the extent of overlap between the electron–hole recombination zone and the organic/metal interface by suppressing electron mobility.•Intersystem crossing that is induced by spin–orbital coupling at the organic/metal interface increase with the extent of overlap leading to the observed high-field decay. We explored mechanisms for the high-field (|B|>50mT) decay of organic magneto-electroluminescence. The organic/metal interface in pristine tris (8-hydroxyquinolinato) aluminum-based organic light-emitting diodes was modified by changing the metal cathodes and their deposition methods. The metals investigated were Al, Au, and Cu and the methods used include molecular beam deposition, thermal resistive evaporation, and electron beam evaporation (EBE), respectively. Experimental results revealed that the high-field decay can be observed at room temperature when the cathode is: (i) Cu deposited by EBE or (ii) Au deposited by any of the three deposition methods. Furthermore, this decay is different from the previously reported high-field decay that originates from triplet–triplet annihilation, triplet-charge reaction processes or Δg mechanism. We suggest that the magnetic field can increase the extent of overlap between the electron–hole recombination zone and the organic/metal interface by suppressing electron mobility. The spin–orbital coupling at the organic/metal interface consequently induces intersystem crossing to increase with magnetic field leading to the observed high-field decay.